Narrativas de vida em stop motion – uma experiência de ensino de língua portuguesa em práticas de multiletramento no ensino fundamental - Matos, Fabiana Santos de Sousa (2018)
This paper aim is to investigate the productivity of teaching practices, which allow promoting the study of linguistic and discursive resources in texts production that encourage the language social use. The research was performed with a 8th grade class from a state school located in Salgado/SE. Based on a diagnosis performed at the beginning of school year, it was possible to identify that the students had some difficulty producing narrative texts about facts they lived with their families. They presented difficulties mainly to elaborate a complicating action that would culminate in a suitable closure to the proposed action in a specified narrative time and space. It was taken as basis the dialectical character of the language (BAKHTHIN, 2006), the conception of writing as a process (PASSARELI, 2012), the consciousness about how important the narratives on life and memoirs are to build our identity and to share knowledge (BOSI, 1994), withal the need to make the teaching-learning techniques more meaningful by using multiliteracies (ROJO, 2012). Then, it was organized some didactic activities to produce animations, using the stop motion technique, based on retold stories lived by elders residing in the city – the purpose was to voice the elders and to provide interchange of life experiences, inside the school context. In addition, through the learning-teaching process, a pedagogical guide was produced purposing to allow dialogic relations with other teachers from basic education. It is important to notice that in this pedagogical practice is necessary for the teacher to take on the profile of a researcher and to be an involved agent, which is the reason why the action research orientations, according to Tripp (2006), were used. Summarizing, the methodology was organized in five steps: the first one was an investigation about the skills of the students and they produced, in class, narrative texts to be analyzed. In the second step, the students participated in a workshop to learn how to use the stop motion tool and about the short films gender. After that, they studied about narrative texts on life and memoirs as the third step. The fourth one was texts production by registering told stories, which were used as basis to make scripts for the short films. Then, in the fifth step, they participated in another workshop and, in groups, produced animations that were shared with everyone involved in the project. At the end, we observed that by using the didactic proposal presented, it was possible to involve students in language practices that exceeded school borders and made possible writing activities with a social, historical and cultural function through the production of narratives on life and memoirs. Through this research was possible to perceive the relevance of multiliteracies to the Portuguese language teaching by allowing meaningful, dynamic and creative activities while connecting school subjects and daily situations. Moreover, that was possible because the activities depart from oral texts, collected in informal moments, to produce multisemiotic texts, which also allowed all parts involved in this research to be valued (the elders, the students, and the school community).